2012
DOI: 10.1128/aem.00705-12
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance in Escherichia coli Isolates from Raccoons (Procyon lotor) in Southern Ontario, Canada

Abstract: ABSTRACTWe conducted a cross-sectional study to determine the prevalence of antimicrobial resistance (AMR) in fecalEscherichia coliisolates from raccoons (Procyon lotor) living in Ontario, Canada. From June to October 2007, we trapped raccoons in three areas: one primarily urban site around Niagara, one primarily rural site north of Guelph,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 23 publications
7
26
1
Order By: Relevance
“…coli in raccoon fecal samples from swine farms and conservation areas. This is consistent with what has been found when comparing raccoon fecal samples in rural and urban areas in Ontario [32], but in contrast to Allen et al [10] who found a higher prevalence of resistant E . coli isolates in mice living on swine farms (48%) than residential areas in Ontario (5%; [10]).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…coli in raccoon fecal samples from swine farms and conservation areas. This is consistent with what has been found when comparing raccoon fecal samples in rural and urban areas in Ontario [32], but in contrast to Allen et al [10] who found a higher prevalence of resistant E . coli isolates in mice living on swine farms (48%) than residential areas in Ontario (5%; [10]).…”
Section: Discussionsupporting
confidence: 92%
“…coli from samples, and the Canadian Integrated Program for Antimicrobial Resistance Surveillance (CIPARS) AMR Lab at the National Microbiology Laboratory of Guelph (formerly the Laboratory for Foodborne Zoonoses (LFZ)), Public Health Agency of Canada (Guelph, Ontario, Canada) conducted the susceptibility testing. Methods used have been previously described [32]. Up to three isolates of E .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pattern of sensitivity was also affected with the type of infection, as ESBL producers had high rate of resistance to cephalosporin and penicillin groups as compared to non ESBL producers. CM Jardine (2012) reported that there were larger multiple antibiotic resistance of E. coli isolated in urban areas than from rural areas. Ramteke (1997) studied the antibiotic resistance of 448 coliforms isolated from drinking water and their tolerance to heavy metals.…”
Section: Discussionmentioning
confidence: 99%
“…7 %) and baboons in Tanzania (up to 6 %) (Routeman et al 1985). However, the value is lower than or similar to those in E. coli isolated from raccoons (Procyon lotor) in Canada (from 17 % to 54 %) (Jardine et al 2012), in E. coli and Salmonella isolated from Russian rooks (Corvus frugilegus) in the Czech Republic (13 %) (Literák et al 2007), in E. coli isolated from sympatric wild rodents in the United Kingdom (20 %) (Williams et al 2011), in E. coli of wild rats (Rattus spp.) in Trinidad (36.3 %) (Nkogwe et al 2011), in E. coli of rats (Rattus spp.)…”
Section: Antibiotic Resistancementioning
confidence: 98%